Developing a structured competency framework for nursing staff in a regional anaesthesia block room...British Association of Day Surgery (BADS) Annual Conference, June 4-5, 2026, London, United Kingdom. - Smith, Sharon; McIntosh, Carole; Mackay, Nicola; Prior, Lee-Ann; Page, Christiana; Hudman, Lindsay; Macpherson, David (Ambulatory Surgery, 2026)
Introduction The introduction of regional anaesthesia (RA) block rooms has transformed perioperative care by enabling parallel processing, improving theatre efficiency, and expanding access to awake day case surgery for higher-risk patients. Safe, sustainable delivery requires a skilled nursing workforce with clearly defined competencies, including recognising complications and providing monitoring under delegated responsibility, as outlined by RA-UK (Neilly & Womack, 2024) and the Royal College of Anaesthetists GPAS Chapter 8 (RCoA, 2025). A standardised, reproducible competency framework was developed alongside launch of a new local block room service. Methods A multidisciplinary team developed a competency framework aligned with national guidance and local standard operating procedures. Training included consultant-led tutorials, mandatory online modules, and supervised clinical practice. Core competencies encompassed patient preparation, monitoring, aseptic technique, ultrasound safety, recognition of complications such as local anaesthetic systemic toxicity (LAST), and escalation of concerns. A simulation session on LAST management was incorporated, with pre- and post-teaching questionnaires evaluating nursing confidence and preparedness. Results The framework was successfully implemented across nursing staff transitioning into the block room role. Following the SIM session, nurses reported improved confidence in managing block room emergencies. All 26 post-teaching respondents rated the session as 'Very Good' or 'Excellent', and all would recommend it to colleagues. Conclusions A competency-based framework provides a safe, scalable, and reproducible approach to training nursing staff in a regional anaesthesia block room. Simulation-based learning enhanced nursing confidence and supported self-reflection. This model promotes service sustainability and offers a transferable template for centres developing block room services.